Early Disc Dislodgement of a Mitral Björk-Shiley Prosthesis - Eguaras, Manuel G. (1984)
Because of its excellent durability, low-flow gradient and low incidence of valve-related complications, the Björk-Shiley prosthesis is one of the most widely used valve prostheses in the world. Component failures are rare with this prosthesis. The following report, however, described a case of early disc dislodgement of a mitral Björk-Shiley prosthetic valve.